Determination of Tensile Strength of Asphalt Binders (ABS) and Work of Adhesion (WaL,S) of Asphalt Binders, using Contact Angle Determinations. - Salazar Delgado, Jorge Alberto (2025)
Due to problems related to water in many pavements around the world it has been searched a way to improve the materials that compose asphalt mixtures. For this purpose different test methods have been developed to measure the properties of the materials related with moisture damage. The test methods that are described are known as goniometry test and asphalt bond strength test (ABS). Many researches in this field are focused on the physicochemical properties of asphalts related with adhesion failure. This article aims to describe two of the main test methods that are used in laboratories in order to measure the work of adhesion in asphalt binders and emulsions. Procedures described here can be of interest to engineers and professionals that work in pavement design and related areas.